UTAR event management system - Phoon, Pei Yi (2024)
This project focuses on web application development and event management within a university setting, addressing challenges related to student engagement and communication. The primary issue is that students often miss crucial event notifications due to the high volume of emails they receive, leading to lower attendance and participation in campus events. To address this, the UTAR Event Management System was developed using PHP and Python for backend operations, HTML, CSS, and JavaScript for frontend design, and MySQL for database management. The system features include user registration, event browsing, event creation, a notification system, and user feedback mechanisms. The research process involved designing a user-friendly interface, implementing backend functionalities, and integrating a local notification system to ensure timely updates and simplify the registration process. User acceptance testing was conducted to evaluate the system's effectiveness in enhancing engagement and improving event management. Results indicate that the system significantly improves notification visibility and streamlines the registration process, leading to increased student participation and operational efficiency for event organizers. User feedback confirms that the platform effectively reduces the likelihood of missing important event notifications. In conclusion, the UTAR Event Management System successfully addresses the problem of overlooked notifications and enhances campus event management. Its main contribution lies in improving communication and engagement through a user-friendly platform. Future enhancements could include upgrading to push notifications and integrating QR code or ticket validation features to further optimize the user experience.